Effects Of Confining Stress During Curing And Shearing On Shear Strength Of Lime-Cement Improved Clays - Solve Hov; Bjørn Kristian Fiskvik Bache; Ingrid Engeset; Per-Anders Mortensen; Priscilla Paniagua; Arnfinn Endal (Deep Foundations Institute, 2022)
During the last decades, it has become common practice in the Nordic countries to use dry deep mixing in soft clays with lime and cement in for example deep excavation pits in soft clay, or as a reinforcement of the passive zone within sheet pile walls. The shear strength of stabilised soils is affected by the stress conditions during curing and shearing. However, this is normally not taken into consideration. As the strength of the stabilised clay is stress dependent, excavation of the overlying soil will lead to a reduction of the confining stresses in the underlying stabilised soils which means that the shear strength will also be reduced. Under embankments on the other hand, the effect is reversed as the shear strength will be increased. In this study, laboratory tests have been performed on stabilised soils cured and tested under different stress conditions to quantify the stress effects in a Norwegian sensitive clay. In addition, direct simple shear tests on samples from in situ columns have been made with varying normal stresses. Results are presented showing an increase of shear strength of the stabilised soil with increased curing stresses, and an even higher increase with increased confining stress during shearing. The results are compared to field measurements along with a discussion of practical application of the findings.